1984
DOI: 10.1530/jrf.0.0710259
|View full text |Cite
|
Sign up to set email alerts
|

An in-vivo method for estimating inhibin production by adult rat testes

Abstract: Summary. The concentrations of inhibin in samples of rat testicular venous and arterial blood and interstitial fluid were measured by an in-vitro bioassay using pituitary cells in culture in which the standard was an ovine testicular lymph preparation (assigned potency 1 unit/mg). Inhibin levels were undetectable ( < 2 U/ml) in both blood samples but reached a mean concentration of 120 \ m=+-\ 7 U/ml in testicular interstitial fluid. After unilateral efferent duct ligation the rate of inhibin accumulation in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…Glycerol doses of 25 µ , 100 µ and 400 µ lowered testicular inhibin activity by 24%, 68% and 90%, respectively. These findings suggest that inhibin is produced in the Sertoli cell and are in agreement with previous data obtained in vitro (Steinberger & Steinberger, 1976;LeGac & de Kretser, 1982) and in-vivo experiments (de Jong & Sharpe, 1977;Au et al, 1984Au et al, , 1986. Peripheral concentrations of immunoreactive inhibin were reduced by 10%, 25% and 57%, respectively, with increasing doses of glycerol.…”
Section: Discussionsupporting
confidence: 92%
“…Glycerol doses of 25 µ , 100 µ and 400 µ lowered testicular inhibin activity by 24%, 68% and 90%, respectively. These findings suggest that inhibin is produced in the Sertoli cell and are in agreement with previous data obtained in vitro (Steinberger & Steinberger, 1976;LeGac & de Kretser, 1982) and in-vivo experiments (de Jong & Sharpe, 1977;Au et al, 1984Au et al, , 1986. Peripheral concentrations of immunoreactive inhibin were reduced by 10%, 25% and 57%, respectively, with increasing doses of glycerol.…”
Section: Discussionsupporting
confidence: 92%
“…This confirms the results of earlier studies that testosterone increases seminiferous tubule fluid production after efferent duct ligation (45,46). Despite this restoration of tubule diameter, seminiferous tubule length is not restored [1590 cm (Hi 0 ) vs. 2240 cm (Ti 0 )], suggesting that the maintenance of tubule length requires a pituitary factor.…”
Section: Elongated Spermatidssupporting
confidence: 89%
“…The increase in plasma levels of inhibin may be similar to efferent duct ligation indicating that the inhibin secreted into the seminiferous tubule lumen is trapped [4]. However, the accumulated inhibin did not appear to influence FSH secretion significantly, probably because of the integrity of the blood-test barrier and the failure of the raised intratubular levels to affect an increase in the secretion of inhibin across the base of the Sertoli cells into testicular lymphatics [5]. Nevertheless, others have suggested that the passage of inhibin into the rete testis fluid and its subsequent absorption represents an important pathway by which inhibin reaches the circulation [27].…”
Section: Discussionmentioning
confidence: 93%
“…Bilateral vasectomy was created surgically (treated group) and intact rats were used as control (control group). On days 3,5,7,14,30, 60, and 90 after surgery, plasma concentrations of FSH, LH, inhibin, and testosterone were measured by radioimmunoassay, and sperm motility characteristics were measured by computer-assisted sperm analysis (CASA). The results show that weights of epididymides significantly increased in vasectomized rats as compared to control rats.…”
mentioning
confidence: 99%